f'(x) = 6x gives the gradient of the tangent.
When x = 2, the gradient is 12.
The tangent at (2,12) is therefore:
y = 12x + c ..........(1)
Since y = 12 when x = 2:
12 = 24 + c
c = - 12.
Substituting this in (1):
y = 12x - 12.
2007-06-02 11:02:29
·
answer #1
·
answered by Anonymous
·
0⤊
0⤋
First, find the derivative of F at x=2:
F'(x) = 6x
F'(2) = 12
This gives you the slope of the tangent line. It also passes through the point (2, 12), so using the point-slope form:
y-12 = 12(x-2)
y-12 = 12x - 24
y=12x-12
This is the equation of the tangent line, so we are done.
2007-06-02 11:03:50
·
answer #2
·
answered by Pascal 7
·
0⤊
0⤋
f(x) = 3x^2
f'(x) = 6x
f'(2) = 6(2) = 12
The gradient or slope of f(x) at (2,12) is 12.
y=mx+c
12=12(2)+c
c = 12 - 24
c = -12
So the equation of the tangent to the line at (2,12) is:
y = 12x - 12
2007-06-02 11:19:27
·
answer #3
·
answered by Kemmy 6
·
0⤊
0⤋
f ` (x) = 6x
f ` (2) = 12 = m
y - b = m.(x - a)
y - 12 = 12.(x - 2)
y = 12x - 12 is equation of tangent that passes thro` (2,12)
2007-06-02 19:55:42
·
answer #4
·
answered by Como 7
·
0⤊
0⤋
y = 3x^2
dy/dx = 6x
the slope ( m ) = 6x 2 = 12
equation of tangent is y - y1 = m(x - x1)
y - 12 = 12( x - 2)
y - 12 = 12x -24
y = 12x -24 + 12
y = 12x -12
2007-06-02 11:33:01
·
answer #5
·
answered by muhamed a 4
·
0⤊
0⤋
f(x)=3x^2
f'(x)=6x, evaluate at x=2
f'(2)=12 (slope)
equation of tangent line: y-12 = 12 (x-2)
y=12x-24+12
y=12x-12
y=12(x-1)
2007-06-02 11:06:07
·
answer #6
·
answered by anggira dhita 2
·
0⤊
0⤋